Overboard eaudiobook - Paretsky, Sara (V. I. Warshawski, 2022)
""Readers can find comfort in the dedication V.I. gives the cries for help she hears from friends, neighbors, and strangers... Very few series authors deliver as masterfully as Sara Paretsky." — San Francisco Book Review Legendary detective V.I. Warshawski uncovers a nefarious conspiracy preying on Chicago's weak and vulnerable, in this thrilling novel from New York Times bestseller Sara Paretsky On her way home from an all-night surveillance job, V.I. Warshawski's dogs lead her on a mad chase that ends when they discover a badly injured teen hiding in the rocks along Lake Michigan. The girl only regains consciousness long enough to utter one enigmatic word. V.I. helps bring her to a hospital, but not long after, she vanishes before anyone can discover her identity. As V.I. attempts to find her, the detective uncovers an ugly consortium of Chicago powerbrokers and mobsters who are prepared to kill the girl. And now V.I.'s own life is in jeopardy as well. Told against the backdrop of a city emerging from its pandemic lockdown, Overboard lays bare the dark secrets and corruption buried in Chicago's neighborhoods in a masterly fashion.